Проблема лексичної інтерпретації при опрацюванні природномовних текстів - Катренко, С. А. (Видавництво Національного університету “Львівська політехніка”, 2002)
Розглянуто проблему неоднозначності при інтерпретації слів, наведено приклади речень та подані способи її усунення, а також подано класифікацію методів, що використовуються для розв'язання цієї проблеми.

Word sense disambiguation (WSD) is an open problem in field of computational linguistics. This article presents variety of lexical interpretation instances, which is often based on the words polycemy. It also gives the classification of word sense disambiguation methods. The supervised training methods and unsupervised training methods are described as well.
Keywords: 681.3